Helping farmers adapt to climate and cropping system change through increased access to sorghum genetic resources adapted to prevalent sorghum cropping systems in Burkina Faso - Brocke, Kirsten vom; Trouche, G.; Weltzien, Eva; Kondombo-Barro, C.P.; Sidibé, A.; Zougmoré, Robert B.; Gozé E (Cambridge University Press, 2014)
Sorghum (Sorghum bicolor (L.) Moench) is a major staple crop of Burkina Faso where farmers continue to cultivate photoperiod-sensitive guinea landraces as part of the strategy to minimize risk and ensure yield stability. In the Boucle du Mouhoun region, however, sorghum farmers appear to have insufficient varietal choice due to cropping systems having shifted towards more intensive cultivation of cotton and maize, and rainfall patterns having decreased over the past decade. In search for new varietal options that can respond to this changing context, researchers decided to give farmers access to ex-situ national collections along with the opportunity to evaluate recent improved varieties. From 2002 to 2007, researchers and farmers worked closely together to implement on-farm testing, including varietal selection trials, crop management and multi-locational trials. Farmers’ choices tend to differ among groups, villages and years, with the exception of four particular landraces: two originating from a collection carried out in the Mouhoun region more than 30 years previous to this research, and two other landraces that came from the dissimilar agro-ecological zones of Burkina Faso. These four were the most commonly selected landraces out of 36 cultivars that covered both improved and landrace varieties. Farmers’ selection criteria were focused on adaptation to agro-climatic conditions as well as specific grain qualities for processing and consumption. The potential usefulness of each variety was verified via multi-locational trials. The paper also shows that wide dissemination of experimental seed, not just across the Mouhoun region but also at a national scale, was largely achieved through collaboration with a strong farmer organisation in conjunction with farmer training programs focused on the on-farm seed production and the commercialisation of this seed.